2018
DOI: 10.1038/s41413-018-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss from Wnt inhibition mitigated by concurrent alendronate therapy

Abstract: Dysregulated Wnt signaling is associated with the pathogenesis of cancers, fibrosis, and vascular diseases. Inhibition of Wnt signaling has shown efficacy in various pre-clinical models of these disorders. One of the key challenges in developing targeted anti-cancer drugs is to balance efficacy with on-target toxicity. Given the crucial role Wnts play in the differentiation of osteoblasts and osteoclasts, acute inhibition of Wnt signaling is likely to affect bone homeostasis. In this study, we evaluated the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 33 publications
6
72
0
1
Order By: Relevance
“…We speculate that one major evolutionary pressure on the function and expression of xenobiotic resistance mechanisms is the need to protect the microenvironment of the intestinal stroma from ingested toxins and microbial metabolites. Similar to the intestine, bone homeostasis is highly dependent on Wnt signaling, and PORCN inhibitors indeed affect bone regeneration (Madan et al, 2018). This suggests that evolutionary pressures imposed by local environmental factors drive the development of drug resistance limited to the intestinal stroma.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that one major evolutionary pressure on the function and expression of xenobiotic resistance mechanisms is the need to protect the microenvironment of the intestinal stroma from ingested toxins and microbial metabolites. Similar to the intestine, bone homeostasis is highly dependent on Wnt signaling, and PORCN inhibitors indeed affect bone regeneration (Madan et al, 2018). This suggests that evolutionary pressures imposed by local environmental factors drive the development of drug resistance limited to the intestinal stroma.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that long-term exposure to a PORCN inhibitor in vitro selected for a AXIN1-mutant clone in a RSPO3-translocated colorectal cancer cell line and the AXIN1 mutation drove acquired resistance to the PORCN inhibitor [20]. Moreover, on-target adverse effects of Wnt pathway blockade by PORCN inhibitors, including bone loss and dysgeusia, were observed in a preclinical study and clinical trials [21][22][23]. One strategy to overcome drug resistance and reduce adverse effects is synergistic drug combinations, through which lower drug doses can be used to achieve improved anticancer efficacy.…”
Section: Introductionmentioning
confidence: 95%
“…4a, b). As one goal of the study was to minimize the on-target side effects of PORCN inhibitor, we used a relatively low dose (5 mg/kg/day) of ETC-159 based on our prior studies [19,21]. In total, 5 mg/kg ETC-159 and 50 mg/kg GDC-0941 as single-agent treatment suppressed tumor growth by 68% and 51%, respectively, while the combination treatment suppressed tumor growth by 94%.…”
Section: Dual Wnt and Pi3k/mtor Pathway Inhibition Potently Blocks Inmentioning
confidence: 99%
“…To date, WNT-targeted drugs have performed poorly in early phase clinical studies, owing to on-target dose-limiting toxicity, including bone fractures (51). Recent work has shown that combination of RANKL and PORCN inhibitors provide potent WNT pathway suppression while avoiding adverse bone-related effects (23). Based on this data, new combination trials have been launched, specifically targeting RSPO3 fusion CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term treatment with WNT974 can cause intestinal and bone damage in mice (22,23). To enable potent and sustained WNT suppression in tumor cells without effects on surrounding tissues, we used the regulatable shApc model, whereby withdrawal of dox from chow drives rapid APC restoration and potent WNT pathway suppression (10,11).…”
Section: The In Vivo Tumor Microenvironment Is Sufficient To Prime Cementioning
confidence: 99%